1988
DOI: 10.1111/j.1525-1470.1988.tb01165.x
|View full text |Cite
|
Sign up to set email alerts
|

Ichthyosis and Neutral Lipid Storage Disease (Dorfman‐Chanarin Syndrome)

Abstract: Ichthyosis and neutral lipid storage disease (INLSD) is a nonlysosomal, multisystemic, triglyceride storage disorder. It is characterized by nonbullous congenital ichthyosiform erythroderma (NBCIE), leukocyte vacuoles, and variable involvement of the liver, muscles, eyes, and central nervous system. In our patient fat-containing vacuoles were also demonstrated in the epidermis. In patients with NBCIE, the diagnosis of INLSD is readily made by direct examination of a peripheral blood smear demonstrating cytopla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…DCS comprises nonbullous congenital ichthyosis, leucocyte vacuoles, and variable involvement of the liver, muscles, eyes, and central nervous system [Venencie et al, 1988].…”
Section: Discussionmentioning
confidence: 99%
“…DCS comprises nonbullous congenital ichthyosis, leucocyte vacuoles, and variable involvement of the liver, muscles, eyes, and central nervous system [Venencie et al, 1988].…”
Section: Discussionmentioning
confidence: 99%
“…NBIE is also a feature of Dorfman-Chanarin syndrome, an autosomal recessive neutral lipid storage disorder involving various organ systems, including the eyes [Venencie et al, 1988]. Diagnosis is by demonstration of cytoplasmic lipid vacuoles within most granulocytes and monocytes.…”
Section: Discussionmentioning
confidence: 98%
“…Durdu et al also observed lipid droplets in the cytoplasm of keratinocytes following a Tzanck smear test 56 . In addition, Arora et al noted that although lipid droplets were absent in the peripheral blood and bone marrow cells of their male patient, an electron microscope examination of the skin biopsy revealed lipid droplets 57–62 . Lipid droplets in cells play an important role in energy homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Verma et al [40] M 17 India yes fatty liver c.752A > C Nakhaei et al [41] 56 In addition, Arora et al noted that although lipid droplets were absent in the peripheral blood and bone marrow cells of their male patient, an electron microscope examination of the skin biopsy revealed lipid droplets. [57][58][59][60][61][62] Lipid droplets in cells play an important role in energy homeostasis. Theses vacuoles store excess energy in the form of TG and in the event of an energy deficit, these TGs will be hydrolysed to release free FAs and glycerol.…”
Section: Liver Disease Liver Phenotype Genotype/mutationmentioning
confidence: 99%